2004
DOI: 10.1037/0882-7974.19.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Frailty in Older Adults and the Protective Role of Positive Affect.

Abstract: The aim of this study was to examine the longitudinal association between positive affect and onset of frailty for 1,558 initially nonfrail older Mexican Americans from the Hispanic Established Populations for Epidemiological Studies of the Elderly database. The incidence of frailty increased 7.9% during the 7-year follow-up period. High positive affect was found to significantly lower the risk of frailty. Each unit increase in baseline positive affect score was associated with a 3% decreased risk of frailty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
3
12

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 55 publications
10
145
3
12
Order By: Relevance
“…Low positive affect is particularly problematic for individuals of this age group. Deficits in this state have been shown to be associated with poorer cognitive functioning (Hill et al, 2005) and poorer health outcomes (Ostir et al, 2004). The other significant difference between centres concerned higher negative affect among the participants in the other older sample at Grenoble.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low positive affect is particularly problematic for individuals of this age group. Deficits in this state have been shown to be associated with poorer cognitive functioning (Hill et al, 2005) and poorer health outcomes (Ostir et al, 2004). The other significant difference between centres concerned higher negative affect among the participants in the other older sample at Grenoble.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of increased levels of positive affect were also shown among elderly Mexican-Americans. Ostir et al (2004) reported higher levels of positive affect were associated with lower risk of physical decline across a 7-year period. Such findings are consistent with those for younger samples (Pettit et al, 2001).…”
Section: Introductionmentioning
confidence: 89%
“…A causa disso pode estar ligada às alterações neuromusculares como a sarcopenia com mudanças na qualidade de fibras musculares e nervosas, e diminuição do controle central das habilidades visuais, vestibulares e proprioceptivas prejudicando, por exemplo, o equilíbrio 26,27 . Em relação à perda de peso não-intencional, apenas 6,3% da amostra obteve esse critério.…”
Section: Discussionunclassified
“…Just as depression has been associated with negative health outcomes, positive emotions are associated with favourable health outcomes in several disease types (Keyes, 2004;Maruta, Colligan, Malinchoc, & Offord, 2000;Ostir, Markides, Black, & Goodwin, 2000;Ostir et al, 2001a;Ostir et al, 2002;Ostir, Ottenbacher, & Markides, 2004). The prevalence of cardiovascular disease was lowest among those who were mentally healthy (defined as flourishing), but highest among those who were depressed and languishing (devoid of well-being but not depressed), in a study of over 3000 adults (Keyes, 2004).…”
Section: Associations With Depression and Chdmentioning
confidence: 99%